E-Module Project Based Learning (PjBL) using Sigil in Basic Vocational Subjects - Rina Sepriana (LPPM Universitas PGRI Semarang, 2025)
There is no learning media that uses the Sigil application, so learning media was created using the Sigil applicationaims to test the level of validity, practicality, and effectiveness of the Project Based Learning (PjBL) E-Module Using Sigil in the Basic Vocational Subject for Grade X Students. The development model in this study uses the development model (ADDIE) with the following steps: (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evaluate. The research subjects were 31 people. The validity test of the E-Module Using Sigil in the Basic Vocational subject obtained a result of 92.73%, with the interpretation of very valid to use. The practicality test of the E-Module using Sigil in the Basic Vocational subject obtained a result of 93.81%, with the interpretation of very practical to use. Meanwhile, the overall effectiveness test results for the E-Module using Sigil in the Basic Vocational subject were 89.29% very effective to use. Thus, it can be concluded that the Project Based Learning (PjBL) E-Module using Sigil in the Basic Vocational subject has been tested for its feasibility, excellence, and can be used in learning activities in the Basic Vocational subject for Class X at SMKN 1 Singkarak.